A survey of Fusobacterium nucleatum genes modulated by host cell infection. Issue 2 (29th October 2019) - Cochrane, Kyla; Robinson, Avery V.; Holt, Robert A.; Allen-Vercoe, Emma
Abstract : Here, we report comprehensive transcriptomic profiles from Fusobacterium nucleatum under conditions that mimic the first stages of bacterial infection in a highly differentiated adenocarcinoma epithelial cell line. Our transcriptomic in vitro adenocarcinoma approach allows us to measure the expression dynamics and regulation of bacterial virulence and response factors in real time, and is a novel strategy for clarifying the role of F. nucleatum infection in colorectal cancer (CRC) progression. Our data show that: (i) infection alters metabolic and functional pathways in F. nucleatum, allowing the bacterium to adapt to the host-imposed milieu; (ii) infection also stimulates the expression of genes required to help induce and promote a hypoxic and inflammatory microenvironment in the host; and (iii) F. nucleatum invasion occurs by a haematogenous route of infection. Our study identifies novel gene targets from F. nucleatum that are activated during invasion and which may aid in determining how this species invades and promotes disease within the human gastrointestinal tract. These invasion-specific genes may be useful as biomarkers for CRC progression in a host and could also assist in the development of new diagnostic tools and treatments (such as vaccines or small molecule drug targets), which will be able to combat infection and inflammation in the host while circumventing the potential problem of F. nucleatum tolerization.